Keeping Food Alive: Surplus Food Management - Sert, Sedef; Garrone, Paola; Melacini, Marco (European Journal of Sustainable Development, 2014)
This paper is motivated by the paradoxical reality of food waste in a world of food insecurity, which is an important issue even for developed countries. Today, in Europe, nearly 43.6 million people are estimated to be food insecure, while European countries are reported to generate 179 kg per capita of food waste every year. Previous empirical studies highlight the potential of surplus food management, i.e. managerial processes and practices that strike a balance between social, environmental and economic goals and avoid safe food that is not sold or consumed degrade into waste. A multidisciplinary literature is reviewed in order to present the current state of art with a special attention on food redistribution for social purposes. In particular, I focus on differences between surplus food and food waste and discuss benefits and costs of surplus food redistribution to the disfavored population. Key Words: food, waste, surplus, recovery, agriculture